ðŸ‘‰ Try now NerdPal! Our new math app on iOS and Android

# Solve the inequality $\frac{2}{3}x-\frac{1}{2}\left(4x-1\right)\geq x+2\left(x-3\right)$

## Step-by-step Solution

Go!
Math mode
Text mode
Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
θ
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

###  Videos

$x\leq \frac{3}{2}$
Got another answer? Verify it here!

##  Step-by-step Solution 

Specify the solving method

1

Multiply the single term $-\frac{1}{2}$ by each term of the polynomial $\left(4x-1\right)$

$\frac{2}{3}x-2x+\frac{1}{2}\geq x+2\left(x-3\right)$

Learn how to solve one-variable linear inequalities problems step by step online.

$\frac{2}{3}x-2x+\frac{1}{2}\geq x+2\left(x-3\right)$

Learn how to solve one-variable linear inequalities problems step by step online. Solve the inequality 2/3x-1/2(4x-1)>=x+2(x-3). Multiply the single term -\frac{1}{2} by each term of the polynomial \left(4x-1\right). Combining like terms \frac{2}{3}x and -2x. Multiply the single term 2 by each term of the polynomial \left(x-3\right). Combining like terms x and 2x.

$x\leq \frac{3}{2}$

SnapXam A2

Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
θ
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

### Main Topic: One-variable linear inequalities

Algebraic inequalities that have just one variable.